Westerly reorganization driven by orbital forcing: Late Miocene aridification in the Tarim Basin, Central Asia - Dong Wang; Qingqing Qiao; Chuang Xuan; Zhuangzhuang Lv; Sunyi Dong; Gangqiang Li; Long Ma; Yudong Chen; Zhanwei Lin; Zhongyin Gao (Global and Planetary Change, 2026)

Direct oxidation of wastewater degradation and hydrogen production simultaneously by a reverse electrodialysis system powered by salinity gradient energy - Qiang Leng; Feilong Li; Yihao Ma; Lin Wang; Sainan Li; Chunxiao Zhang; Zhanwei Wang; Xi Wu (Journal of Environmental Chemical Engineering, 2025)

Wastewater degradation driven by the membrane voltage in a closed-loop reverse electrodialysis system integrated with air-gap diffusion distillation technology - Qiang Leng; Feilong Li; Yihao Ma; Chunxiao Zhang; Lin Wang; Zhanwei Wang; Xi Wu (Desalination, 2025)

Examining the impact of common faults on chiller performance through experimental investigation and parameter sensitivity analysis - Zhanwei Wang; Penghua Xia; Sai Zhou; Lin Wang; Jingjing Guo; Xiuzhen Li; Jingfeng Shi; Jianxing Chen (Energy and Buildings, 2024)

Discovery of the tigecycline resistance gene cluster tmexCD3-toprJ1 in Pasteurella multocida strains isolated from pigs in China - Congcong Shi; Zhanwei Zhu; Yuyao Shang; Wenbo Song; Jie Yang; Haixin Bi; Zihao Wang; Rui Xie; Mengfei Zhao; Lin Hua; Huanchun Chen; Bin Wu; et al. (Veterinary Microbiology, 2024)

Feature selection for chillers fault diagnosis from the perspectives of machine learning and field application - Zhanwei Wang; Jingjing Guo; Penghua Xia; Lin Wang; Chunxiao Zhang; Qiang Leng; Kaixin Zheng (Energy and Buildings, 2024)

Blood Transcriptome Analysis Provides Responsive Changes in Gene Expression between Ex Situ and Captive Yangtze Finless Porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Zhichen Cao; Denghua Yin; Zhanwei Li; Yan Yan; Peng Zhang; Sigang Zhang; Danqing Lin; Zhong Hua; Jialu Zhang; Congping Ying; Han Zhang; Pao Xu; et al. (Fishes, 2023)
The Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis, YFP) is an endangered species endemic to the Yangtze River in China, and it is the only freshwater whale in the genus Neophocaena. In terms of protection, three effective conservation strategies exist: in situ conservation, ex situ conservation, and artificial breeding, all of which have been implemented by the Chinese government. Of these, ex situ conservation involves the relocation of Yangtze finless porpoises to semi-natural waters with less human interference, and artificial breeding involves the relocation of Yangtze finless porpoises to a controlled environment that is more strictly managed. To compare and analyze the responsive changes in gene expression of the YFPs between the ex situ and controlled environments, we performed the RNA sequencing of blood tissues from these YFPs. A total of 1201 differentially expressed genes (DEGs) were identified, of which 423 were up-regulated in the ex situ population and 778 were up-regulated in the controlled-environment population. Gene enrichment analysis showed that 1201 DEGs between the ex situ and controlled-environment populations were generally enriched for vision-, digestion- and immune-system-related pathways. Further analysis revealed that several key immune system pathways, such as the chemokine signaling pathway and B cell receptor signal pathway, were activated in the ex situ population. In addition, the key pathways related to vision, including phototransduction and the inflammatory mediator regulation of TRP channels, as well as the pathways related to the digestive system, such as protein digestion and absorption and salivary secretion, were activated in the controlled-environment population. These results suggest that the ex situ populations may respond to complex environmental conditions in semi-natural waters by enhancing their immune function through the increased expression of immune-related genes and that the visual function and protein digestion of the YFPs were improved compared to those of the ex situ population based on the conditions of artificial feeding, such as the higher transparency of the water and regular feeding. This study provides clues for evaluating the adaptability of YFPs to different environments and is a useful reference for future ex situ conservation and artificial breeding.

Evolutionary traits and functional roles of chemokines and their receptors in the male pregnancy of the Syngnathidae - Han Jiang; Zhanwei Zhao; Haiyan Yu; Qiang Lin; Yali Liu (Marine Life Science & Technology, 2023)

Numerical Investigation into the Effect of Damage Openings on Ship Hydrodynamics by the Overset Mesh Technique - Xinlong Zhang; Zhuang Lin; Simone Mancini; Ping Li; Dengke Liu; Fei Liu; Zhanwei Pang (Journal of Marine Science and Engineering, 2019)
Damage stability is difficult to assess due to the complex hydrodynamic phenomena regarding interactions between fluid and structures. Therefore, a detailed analysis of the flooding progression and motion responses is important for improving ship safety. In this paper, numerical simulations are performed on the damaged DTMB 5415 ship at zero speed. All calculation are carried out using CD Adapco Star CCM + software, investigating the effect of damage openings on ship hydrodynamics, including the side damage and the bottom damage. The computational domain is modelled by the overset mesh and solved using the unsteady Reynold-average Navier-Stokes (URANS) solver. An implicit solver is used to find the field of all hydrodynamics unknown quantities, in conjunction with an iterative solver to solve each time step. The Volume of Fluid (VOF) method is applied to visualize the flooding process and capture the complex hydrodynamics behaviors. The simulation results indicated that two damage locations produce the characteristic flooding processes, and the motion responses corresponding to the hydrodynamic behaviors are different. Through comparative analysis, due to the difference between the horizontal impact on the longitudinal bulkhead and the vertical impact on the bottom plate, the bottom damage scenario always has a larger heel angle than the side damage scenario in the same period. However, the pitch motions are basically consistent. Generally, the visualization of the flooding process is efficient to explain the causes of the motion responses. Also, when the damage occurs, regardless of the bottom damage or the side damage, the excessive heel angle due to asymmetric flooding is often a threat to ship survivability with respect to the pitch angle.